Activation of Akt by the Bacterial Inositol Phosphatase, SopB, is Wortmannin Insensitive - Cooper, Kendal G. (Public Library of Science, 2011)
Salmonella enterica uses effector proteins translocated by a Type III Secretion System to invade epithelial cells. One of the invasion-associated effectors, SopB, is an inositol phosphatase that mediates sustained activation of the pro-survival kinase Akt in infected cells. Canonical activation of Akt involves membrane translocation and phosphorylation and is dependent on phosphatidyl inositide 3 kinase (PI3K). Here we have investigated these two distinct processes in Salmonella infected HeLa cells. Firstly, we found that SopB-dependent membrane translocation and phosphorylation of Akt are insensitive to the PI3K inhibitor wortmannin. Similarly, depletion of the PI3K regulatory subunits p85α and p85ß by RNAi had no inhibitory effect on SopB-dependent Akt phosphorylation. Nevertheless, SopB-dependent phosphorylation does depend on the Akt kinases, PDK1 and rictor-mTOR. Membrane translocation assays revealed a dependence on SopB for Akt recruitment to Salmonella ruffles and suggest that this is mediated by phosphoinositide (3,4) P(2) rather than phosphoinositide (3,4,5) P(3). Altogether these data demonstrate that Salmonella activates Akt via a wortmannin insensitive mechanism that is likely a class I PI3K-independent process that incorporates some essential elements of the canonical pathway.